1997
DOI: 10.1007/bf02900305
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, biochemical and subjective parameters in anxiety patients with panic disorder during stress exposure as compared with healthy controls

Abstract: Physiological (heart rate, blood pressure, electrodermal activity), biochemical (epinephrine, norepinephrine, cortisol) and subjective parameters (self-rating score) of 33 patients with panic disorder (diagnoses according to DSM-III-R) before, during and after stress exposure were compared with those of healthy controls. As stressors a video containing frightening scenes (FS), mental arithmetic (MA), a video documenting a patient suffering from a panic attack (PA) and an improvised speech (IS) were applied. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 79 publications
2
19
0
1
Order By: Relevance
“…There are numerous reports of increased physiological arousal or subjective anxiety in anxious patients during conditions of distal threat, for example, during the period that precedes a future psychological or chemical challenges (Alpers et al 2003;Braune et al 1994;Charney et al 1984;Coplan et al 1998;Hoehn et al 1997;Parente et al 2005). Similarly, mere participation in an experiment involving the future delivery of aversive stimuli can generate substantial anticipatory anxiety that can be measured with the startle reflex (Bocker et al 2004;Grillon and Ameli 1998).…”
Section: Clinical Anxietymentioning
confidence: 99%
“…There are numerous reports of increased physiological arousal or subjective anxiety in anxious patients during conditions of distal threat, for example, during the period that precedes a future psychological or chemical challenges (Alpers et al 2003;Braune et al 1994;Charney et al 1984;Coplan et al 1998;Hoehn et al 1997;Parente et al 2005). Similarly, mere participation in an experiment involving the future delivery of aversive stimuli can generate substantial anticipatory anxiety that can be measured with the startle reflex (Bocker et al 2004;Grillon and Ameli 1998).…”
Section: Clinical Anxietymentioning
confidence: 99%
“…This matches findings of Petrowski et al [8], who reported a blunted cortisol reactivity to the TSST with concurrent normal cortisol awakening responses in PD patients compared to HC participants. The similar baseline cortisol levels between PD patients and HC subjects have already been reported elsewhere [29]. Interestingly, baseline cortisol values (–10 min, 0 min) of CIPD patients were slightly higher than those of HC participants (and higher than PD patients), although this difference did not reach statistical significance (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Leyton et al [15] observed greater increases in plasma levels of cortisol in patients compared to controls in response to a psychological stressor. The main problem of other studies using mental stress paradigms was that the stress challenge used did not induce a rise in cortisol levels [16,17,18]. As there was no stress-induced rise in cortisol release in the control groups, a similar pattern of cortisol concentrations observed in patients with panic disorder does not necessarily mean that the stress response is not altered in panic disorder.…”
Section: Introductionmentioning
confidence: 84%
“…Plasma noradrenaline and adrenaline concentrations were found to be either unchanged or elevated in patients at rest [16,19]. In general, plasma catecholamine responses to mental or combined laboratory stress situations did not differ substantially between patients with panic disorder and healthy subjects [19,20,21].…”
Section: Introductionmentioning
confidence: 99%